What drives Bitcoin fees? Using Segwit to assess Bitcoin's long-run sustainability - Colin M. Brown; Jonathan Chiu; Thorsten V. Koeppl (Bank of Canada, 2022)
Can Bitcoin remain tamper proof in the long run? We use block-level data from the Bitcoin blockchain to estimate the impact of congestion and the USD price on fee rates. The introduction and adoption of the Segwit protocol allows us to identify an aggregate demand curve for bitcoin transactions. We find that Segwit has reduced fee revenue by about 70%. Fee revenue could be maximized at a block size of about 0.6 MB when Segwit adoption remains at current levels. At this block size, maximum fee revenue would be equivalent to 1/8 of the current average block reward. Hence, large sustained price increases are required to keep mining rewards constant in the long run.
Keywords: E42; G2; 330; Digital currencies and fintech; Payment clearing and settlement systems